Neuronal and hormonal perturbations in postural tachycardia syndrome - Mar, Philip L.; Raj, Satish R. (Frontiers in Physiology, 2014)
The Postural Tachycardia Syndrome (POTS) is the most common disorder seen in autonomic clinics. Cardinal hemodynamic feature of this chronic and debilitating disorder of orthostatic tolerance is an exaggerated orthostatic tachycardia (≥30 bpm increase in HR with standing) in the absence of orthostatic hypotension. There are multiple pathophysiological mechanisms that underlie POTS. Some patients with POTS have evidence of elevated sympathoneural tone. This hyperadrenergic state is likely a driver of the excessive orthostatic tachycardia. Another common pathophysiological mechanism in POTS is a hypovolemic state. Many POTS patients with a hypovolemic state have been found to have a perturbed renin-angiotensin-aldosterone profile. These include inappropriately low plasma renin activity and aldosterone levels with resultant inadequate renal sodium retention. Some POTS patients have also been found to have elevated plasma angiotensin II (Ang-II) levels, with some studies suggesting problems with decreased angiotensin converting enzyme 2 activity and decreased Ang-II degradation. An understanding of these pathophysiological mechanisms in POTS may lead to more rational treatment approaches that derive from these pathophysiological mechanisms.